An essay: punitiveness and resentment - Crewe, Don (Journal of Theoretical and Philosophical Criminology, 2021)
We have witnessed in the West over the last forty years or so, a rampant increase in the number and severity of penal sanctions. This has been driven, it has been suggested, by a broadening and an intensification of punitive sentiments or punitiveness (Pratt, 2011)). We may take it that what characterizes punitiveness is the desire to punish, however, this idea runs up against serious problems if we don’t know what punishment is, hence in part one of this paper I examine what punishment is taken to be, and what it is taken to be for. I suggest that the only claim about the nature of punishment that really holds water is that it involves the infliction of pain, and punitiveness therefore becomes the desire to inflict pain. Revealing as this does that punishment is not necessarily to be equated with the settling of legal harms, in part two of the paper I address a possible candidate for the desire to inflict pain in the emotion resentment. The suggestion that punitiveness is a particular kind of resentment reveals punitiveness’ role in the structuring of cultures and as a tool of governance.